Response of Cucurbit Fruit Fly (Zeugodacus cucurbitae) Coquilette to Gel Formulations of Protein Bait - Manikantha B Jakkanagoudra; Zadda Kavitha; M. Shanthi; K. Subaharan; C. Vijayaraghavan (Archives of Current Research International, 2025)
In the integrated pest management of fruit flies, trapping is the most practical and effective component. Currently, cucurbit fruit flies are being trapped by employing the male attractant, cuelure. Protein baits attract both male and female fruit flies and they may be explored for their management. The present study was conducted at Agricultural College and Research Institute, TNAU, Madurai, Tamil Nadu during 2022 in which, protein baits were compared with the cuelure for their attraction to fruit flies by using electroantennogram. In field conditions, effectiveness of protein bait is restricted due to water loss by evaporation thus making the bait dry. In view of this, studies were conducted to compare the preference of fruit flies to protein baits & cuelure and evaluated advanced gel formulations of protein bait in attracting fruit flies. In electroantennogram studies, female fruit fly response was found to be better to proteinex bait volatiles followed by soybean bait and cue lure volatiles. Responses of male fruit flies were uniform to proteinex bait and cue lure followed by soybean bait. Among the gel formulations of liquid proteinex bait, using olfactometer, attraction response of pectin and sodium alginate gel formulations was similar to the attraction of liquid protein bait. The response recorded in olfactometer were seen in decreasing pattern while using xanthan gum powder and carrageenan powder gel formulations attracxted more number of fruit flies. In gated cup trap choice test, pectin powder gel formulation attracted more number of fruit flies followed by liquid proteinex bait.